‘New worlds open up’: A qualitative study on Wonder Lab practices in Dutch paediatric palliative care with parents, healthcare professionals, and students - Liesbeth Geuze; Samuel Schrevel; Paula van Driesten – van Roozen; Anne Goossensen (SSM: Qualitative Research in Health)
Within paediatric palliative care, it is essential for families and providers to have open, equal, and trusting relationships. In practice, however, building relationships can be challenging. Investing in better understanding the differences in each other's frames of reference and underlying values seems important. Wonder Lab practices provide a space to explore these differences by focusing together on life phenomena in curious and Socratic ways. Wonder Labs were organised with parents, healthcare professionals, and students involved in Dutch paediatric palliative care. The aim of this study was to develop an understanding of how participants experienced participating in Wonder Labs. We conducted twenty in-depth interviews with Wonder Lab participants and used inductive thematic analysis for data interpretation. Five themes were identified: Slowing down, Appreciating stories, Becoming vulnerable, Opening up and diving in, and Reframing perspectives. Participating in Wonder Labs allowed mothers, healthcare professionals, and students to contribute to deepening experiences and gain an expanded understanding of what is at play in caring for children with life-limiting and life-threatening conditions. Through working in pluralised groups, frames of reference and understandings complemented each other and could change. Participants often adopted a more open attitude towards others involved in care after participating and adapted day-to-day practices. Deliberating within paediatric palliative care on sensitive issues and their underlying personal and professional beliefs and values must be part of working together, without specific care situations being the catalyst. This may foster the mutual understanding needed in searching for quality of life, death, and bereavement.